Russian Black Sea Trade in Early 19th Century - E. P. Kudryavtseva (Vestnik MGIMO-Universiteta, 2023)
This research article examines the development of trade in Crimea and Novorossiya following their incorporation into Russia. In the early 19th century, the grain trade in these regions had yet to gain momentum due to their limited development. However, ports in Feodosia, Taganrog, and Odessa regularly received ships from Constantinople and the Greek islands, while the port of Sevastopol primarily served military purposes. In 1821, under the decree of Alexander I, a port was established in Kerch to serve as an outpost at the entrance to the Sea of Azov and initiate trade relations with the mountain peoples along the Caucasian coast of the Black Sea. The Russian authorities faced challenges such as arms smuggling and the flourishing slave trade during this period. Establishing trade relations between Crimea and Circassia was intended to promote peaceful interactions with the inhabitants of the Caucasian coast. To facilitate this, the Stewardship of Trade with the Circassians and Abazians was established, regulating ship dispatch to the Caucasian coast and overseeing the operations of markets in Kerch and Bugaz. Relations with the highland communities proved difficult, as they frequently captured Russian ship crews and demanded ransoms. Even after the Treaty of Adrianople in 1829, when these territories became part of the Russian Empire, the local populations resisted submission to the new government, just as they had resisted the authority of the Turkish Sultan previously.